Análisis socioeconómico de los pequeños productores de arroz en el recinto Las Chacras, cantón Lomas de Sargentillo - Morán Pinela, Nayeli Nicole (2024)
Rice production plays a crucial role in Ecuador's economy and food security. Rice is one of the country's main food crops and contributes significantly to the basic diet of the population. It also represents an important source of income for farmers. The objective of the research was to analyze the socioeconomic aspects of small rice farmers in the Las Chacras Campus of the Lomas de Sargentillo canton. The methodology used refers to a mixed approach through a descriptive scope. The techniques used were the survey and the interview. The sample was 40 producers. Among the results obtained, it was found that the majority of producers have a primary education level, do not receive support from the local government, and frequently receive financing through informal loans, among others. The study carried out proposed creating a plan that encompasses the creation of a producer association with the purpose of increasing income, improving quality of life and promoting sustainable development in the community.